2017
DOI: 10.1038/s41467-017-01083-5
|View full text |Cite
|
Sign up to set email alerts
|

Cubic gauche polymeric nitrogen under ambient conditions

Abstract: The long-sought cubic gauche phase of polymeric nitrogen (cg-PN) with nitrogen-nitrogen single bonds has been synthesized together with a related phase by a radio-frequency plasma reaction under near-ambient conditions. Here, we report the synthesis of polymeric nitrogen using a mixture of nitrogen and argon flowing over bulk β-sodium azide or β-sodium azide dispersed on 100 nm long multiwall carbon nanotubes. The cg-PN phase is identified by Raman and attenuated total reflection-Fourier transform infrared spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 16 publications
0
55
0
Order By: Relevance
“…However, the presence of the peak around 2700 cm −1 in 2D position over NCNT sample suggests the long-range ordering of graphitic structure. For NaN 3 /CNT sample, the sharp peak around 1360 cm −1 associated with sodium azide overlaps with the carbon nanotube D (defect) mode [32], which is also observed on NaN 3 /NCNT. Interestingly, the spectrum of PN-CNT sheet clearly depicts a line at 1077 cm −1 , other than those from CNT.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…However, the presence of the peak around 2700 cm −1 in 2D position over NCNT sample suggests the long-range ordering of graphitic structure. For NaN 3 /CNT sample, the sharp peak around 1360 cm −1 associated with sodium azide overlaps with the carbon nanotube D (defect) mode [32], which is also observed on NaN 3 /NCNT. Interestingly, the spectrum of PN-CNT sheet clearly depicts a line at 1077 cm −1 , other than those from CNT.…”
Section: Resultsmentioning
confidence: 67%
“…The morphology of PN species was characterized by TEM as illustrated in Figure 2a. It clearly showed that PN species deposited on the outer-, intra-, and inter-layers of the nanotubes [32,36]. To investigate the thermal stability and quantify the amount of the synthesized PN species, temperature-programmed decomposition (TPD) was performed over different samples as displayed in Figure 2b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, different PN clusters and molecular crystals were theoretically predicted and some were experimentally obtained [14][15][16][17][18][19][20]. In 2017, two main achievements renovated once again the interest in the field, namely the isolation and characterization of cyclo-N − 5 pentazolate [21] and the synthesis of the cubic gauche form of nitrogen under near-ambient conditions [22]. Despite the recent successes, other ways to stabilize (and hopefully store) singleand double-bonded PN clusters were proposed too, in particular molecular confinement.…”
Section: Introductionmentioning
confidence: 99%
“…By spatially confining PN clusters inside the cavity of such materials, thanks to less geometrical freedom as well as non-bonded interactions with the hosting system, the guest fragments may be favorably stabilized and stored. First investigations in this direction have proposed the encapsulation of nitrogen chains inside carbon nanotubes and have theoretically predicted, as well as later experimentally observed, the feasibility of this approach [22][23][24][25][26][27]. Besides carbon nanotubes, other types of carbon nanostructures as well as other nanomaterials have been proposed as valid alternatives [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%